2022
DOI: 10.1111/ijfs.16201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sanxan on the quality of salt‐free frozen‐cooked wheat noodles during freeze–thaw cycles

Abstract: Developing salt-free frozen-cooked wheat noodles (FCNs) has a promising future, and how to eliminate the deficiency of the absence of salt is key to enhance its quality. In this study, based on the unique 'gelforming in cold water and gel strength-strengthening during heating' properties, sanxan was used to improve the quality of salt-free FCNs and the underlying mechanism was initially explored. TPA analysis, colour profile, thermal stability analysis, determination of free sulfhydryl and disulphide bonds con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This indicated that the starch granules in the center of the noodles were not completely gelatinized due to insufficient hydration after cooking. 43 More intact starch granules were present in the center of the HGDN and were tightly wrapped by the gluten network. With the increase in the immersion time, the binding of starch granules and gluten proteins in the noodles gradually decreased, and larger gaps gradually appeared between the two biomolecules.…”
Section: Food and Function Papermentioning
confidence: 99%
“…This indicated that the starch granules in the center of the noodles were not completely gelatinized due to insufficient hydration after cooking. 43 More intact starch granules were present in the center of the HGDN and were tightly wrapped by the gluten network. With the increase in the immersion time, the binding of starch granules and gluten proteins in the noodles gradually decreased, and larger gaps gradually appeared between the two biomolecules.…”
Section: Food and Function Papermentioning
confidence: 99%